THE POWER/KNOWLEDGE INTEGRATION PROCESS OF OPEN COLLECTIVE PAINTING TEAMS - Deng, Lei; Wang, Shanshan (Chinese Journal of Social Science and Management, 2021)
Based on the perspective of knowledge management, this paper studies the content of power/knowledge integration between knowledge transferors in an open group painting creation team with the support of the power/knowledge theory of formalist. This article selected an open collective painting creative team in the field of painting as the research object, with in-depth interviews of the qualitative approach to the team power/knowledge integration process for exploratory research, drawing the following conclusions: (1) Open goals decided the collective painting creation team power/knowledge integration process as a power/knowledge overlapping development integration process; (2) Team relationship is the basis of power/knowledge integration, difference conflict, and coordination factors, which play a regulating role in power/knowledge integration, and conflict demand (individual power/knowledge realization demand) is an important supporting condition for the power/knowledge integration process. Through this study, the knowledge integration content found in this paper can be applied to a broader professional background of team practice. Alternatively, a gap in the power/knowledge integration content around knowledge transferors can be filled.